2024
DOI: 10.1007/s40121-024-00961-y
|View full text |Cite
|
Sign up to set email alerts
|

Two-Drug Regimens Dolutegravir/Lamivudine and Dolutegravir/Rilpivirine Are Effective with Few Discontinuations in US Real-World Settings: Results from the TANDEM Study

Stefan Schneider,
Gary Blick,
Christina Burke
et al.

Abstract: Introduction Dolutegravir/lamivudine (DTG/3TC) and dolutegravir/rilpivirine (DTG/RPV) are fixed-dose, complete, single-tablet, two-drug regimens (2DRs) indicated for HIV-1. DTG/3TC is approved for antiretroviral therapy (ART)-naive people with HIV-1 and virologically suppressed individuals to replace current ART; DTG/RPV is indicated for virologically suppressed individuals as a switch option. Virologic efficacy and effectiveness of these DTG-based 2DRs have been demonstrated in phase 3 clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Detailed methods for the TANDEM study have previously been reported [ 15 ]. Briefly, data were collected from 24 sites in the United States.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed methods for the TANDEM study have previously been reported [ 15 ]. Briefly, data were collected from 24 sites in the United States.…”
Section: Methodsmentioning
confidence: 99%
“…In the US-based, retrospective TANDEM study, 94% (118/126) of treatment-naive individuals achieved virologic suppression after initiation of DTG/3TC, and 83% remained suppressed after a median of 1.3 years of treatment. Only one (< 1%) person discontinued DTG/3TC by data cutoff [ 15 ]. Outcomes for treatment-naive individuals in the TANDEM study who initiated DTG/3TC as part of a test-and-treat strategy or who initiated with high baseline viral loads (defined as 100,000–250,000 copies/ml and > 250,000 copies/ml) are described here.…”
Section: Introductionmentioning
confidence: 99%